1. ## Solve for y

y3 + 5 - y9=1/6

2. ## Solve for y

I Type it in wrong

y/3 + 5 - y/9 = 1/6

3. do you mean:

$\displaystyle 3y+5 -9y = \frac{1}{6}$

if so:

$\displaystyle 3y+5 -9y = 5 - 6y = \frac{1}{6}$

$\displaystyle 6y = 5-\frac{1}{6} = \frac{30}{6}-\frac{1}{6} = \frac{29}{6}$

$\displaystyle y = \frac{29}{36}$

OR do you mean:

$\displaystyle y^3+5-y^9 = \frac{1}{6}$

4. Originally Posted by armygirltiff
y3 + 5 - y9=1/6
Do you mean this?

$\displaystyle 3y+5-9y=\frac{1}{6}$

If so, then multiply the equation by six to get:

$\displaystyle 18y+30-54y=1$

Group the y's and constants on opposite sides

$\displaystyle -36y=-29$

Divide by -36 to get

$\displaystyle y = \frac{29}{36}$

5. no i mean
y/3 + 5 -y/9=1/6

6. Originally Posted by armygirltiff
no i mean
y/3 + 5 -y/9=1/6
In the future put any corrections in the original thread. Do NOT just make a new one!!

-Dan

7. $\displaystyle \frac{y}{3}+5-\frac{y}{9} = \frac{1}{6}$

$\displaystyle 3y+5-y = \frac{9}{6}$ (multiply both sides by 9)

$\displaystyle 2y+5 = \frac{3}{2}$ (simplify)

$\displaystyle 2y = \frac{3}{2}-5$ (subtract 5 from both sides)

$\displaystyle 2y = \frac{-7}{2}$ (simplify)

$\displaystyle y = \frac{-7}{4}$(divide both sides by 2)

8. Originally Posted by armygirltiff
no i mean
y/3 + 5 -y/9=1/6
$\displaystyle \frac{y}{3}+5-\frac{y}{9}=\frac{1}{6}$

Multiply the equation by the lowest common denominator which happens to be 18!

$\displaystyle 6y+90-2y=3$

Combine y's on LS and constants on RS

$\displaystyle 4y=-87$

Divide by 4

$\displaystyle y=\frac{-87}{4}$

9. Originally Posted by iknowone
$\displaystyle \frac{y}{3}+5-\frac{y}{9} = \frac{1}{6}$

$\displaystyle 3y+5-y = \frac{9}{6}$ (multiply both sides by 9)

$\displaystyle 2y+5 = \frac{3}{2}$ (simplify)

$\displaystyle 2y = \frac{3}{2}-5$ (subtract 5 from both sides)

$\displaystyle 2y = \frac{-7}{2}$ (simplify)

$\displaystyle y = \frac{-7}{4}$(divide both sides by 2)
Iknowone, you forgot to multiply 5 by 9!